Influence of Stream‐Subsurface Exchange Flux and Bacterial Biofilms on Oxygen Consumption Under Nutrient‐Rich Conditions. Issue 7 (5th July 2018) - De Falco, N.; Boano, F.; Bogler, A.; Bar‐Zeev, E.; Arnon, S.
Abstract: The lack of a complete understanding of the complex reciprocal interactions between hydrological processes and the structure and function of microbial communities limits our ability to improve the predictions of microbial metabolism in streams. We report here on how overlying water velocity and losing and gaining flux interact with bacterial community structure and its activity to control oxygen consumption in a sandy streambed under high nutrient levels. We used an experimental flume packed with natural sediment and measured the bacterial biomass distribution and oxygen profiles in the streambed and across bed forms. Local oxygen consumption rates were calculated with a 1‐D numerical model (GRADIENT). Bacterial abundance and production rates varied across the bed form within 1 order of magnitude, while their taxonomic classes were similar across bed forms despite variations in flow conditions and sediment disturbance events. However, bacterial production rates were not directly correlated with bacterial abundance. On the other hand, oxygen consumption rates ranged over 4 orders of magnitude across the bed forms and were highly correlated with the vertical exchange flux between the water and the streambed. The results strongly suggest that under high nutrient levels, the system is, in general, transport limited and that predicting oxygen consumption rates depends on local vertical exchange fluxes. Key Points: Biomass distributions varied within 1 order of magnitude across the bed forms and were not strongly correlated with oxygen consumption rates Oxygen consumption rates varied over 4 orders of magnitude and were dependent on the vertical exchange flux at the water‐streambed interface Main bacterial taxonomic classes were similar across bed forms despite variations in flow conditions and sediment disturbance events